2016
DOI: 10.1186/s13033-016-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Important considerations when providing mental health first aid to Iraqi refugees in Australia: a Delphi study

Abstract: BackgroundRefugees are one of the most vulnerable groups in Australian society, presenting high levels of exposure to traumatic events and consequently high levels of severe psychological distress. While there is a need for professional help, only a small percentage will receive appropriate care for their mental health concerns. This study aimed to determine cultural considerations required when providing mental health first aid to Iraqi refugees experiencing mental health problems or crises.MethodUsing a Delp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…While differences in culture and language of host communities and refugees has been reported as reasons explaining the inability of refugees to find jobs in advanced countries (Akua-Sakyiwa, 2017;Guajardo et al, 2016;Joyce & Liamputtong, 2017), this seems not to be the case in this study. Despite shared culture and language which apparently influenced warm reception given to participants by host communities, they were unable to engage in income generating activities.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…While differences in culture and language of host communities and refugees has been reported as reasons explaining the inability of refugees to find jobs in advanced countries (Akua-Sakyiwa, 2017;Guajardo et al, 2016;Joyce & Liamputtong, 2017), this seems not to be the case in this study. Despite shared culture and language which apparently influenced warm reception given to participants by host communities, they were unable to engage in income generating activities.…”
Section: Discussioncontrasting
confidence: 56%
“…In some cases, refugees from conservative cultural and religious societies find it difficult to adapt -a situation which affects their psychological well-being (Basheti, Quinaibi & Malas, 2015;Schick et al 2016). Guajardo et al, (2016), reported that educational programmes and cultural orientations are critical as they enable refugees to understand life in their new communities. Since there is already a shared identity between the people in the Lake Chad, there is no need institutionalising such programmes.…”
Section: Experiences Of Refugees and Its Psychosocial Impactsmentioning
confidence: 99%
“…To our knowledge programs of this kind have not yet been developed. The current findings, when taken with those of our previous research [16, 17, 40], provide the information needed to develop innovative and culturally sensitive programs of this kind that can bridge the gap between Western biomedical models for mental health care and the knowledge and beliefs of resettled refugee populations. This is, in our opinion, the missing step needed to improve mental health outcomes among resettled refugees in Australia.…”
Section: Discussionmentioning
confidence: 53%
“…Certainly increasing the MHL of those who work with refugees is important and needed [16]. A step in this direction has recently been undertaken with the publication and dissemination of guidelines and a training program designed to improve key aspects of MHL relating to PTSD among individuals assisting in the resettlement of Iraqi refugees in Australia [40]. The program seeks to improve participants’ knowledge and understanding of PTSD and other mental health problems while also promoting awareness of the historical, cultural and social factors specific to the experiences of these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The term usually applies to people who are very aware of their condition, despite the psychological and physical deterioration [2]. Psychological distress, posttraumatic stress disorder and major depressive episode have been recognized as the most common mental health issues amongst the uprooted populations [3,4].…”
Section: Introductionmentioning
confidence: 99%